INTERPOLATION METHODS ELANDT-JOHNSON TO ESTIMATE THE COMPLETE MORTALITY TABLE OF THE INDONESIAN YOUTH POPULATION BASED ON THE MORTALITY TABLE COALE-DEMENY - Riningsih, Novia; Widyasari, Rina; Husein, Ismail (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2025)
The growth of the productive age population has continued to increase since 1971 and looks more significant in 2020. In 2010, the youth age group (16-30 years) reached 62.343.755. The population consists of 31.244.215 men and 31.099.540 women. In 2020, the youth age group will increase to 64.470.655 people, with 32.949.184 men and 31.529.270 women. The number of male youth is greater than the number of female youth. However, in 2020, youth health conditions worsened. Many young people experience severe stress and commit suicide due to depression. This will be one of the causes of the decline in young people in Indonesia. Since the Elandt-Johnson interpolation method provides reliable estimates for adult mortality, this study aims to obtain a more accurate, complete life table for Indonesian youth by applying the Elandt-Johnson interpolation method based on the Coale-Demeny West model a-bridged life table, using secondary data from the 2010 and 2020 Population Censuses provided by Statistics Indonesia. From the research results, it is known that the number of young men who survive until the age of 30 is 94.444 and young women who survive until the age of 30 is 95.724, meaning that the number of young women who survive is higher than young men, this means that the number of deaths of young men is higher than that of young women.